Topology, landscapes, and biomolecular energy transport - Justin E. Elenewski; Kirill A. Velizhanin; Michael Zwolak (Nature Communications, 2019)
Understanding vibrational energy transfer in macromolecules has been challenging to both theory and experiment. Here the authors use non-equilibrium molecular dynamics to reveal the relationship between heat transport in a model peptide, emergent nonlinearity, and the underlying free energy landscape.